A Hybrid MADM Approach for the Analysis of the Most Polluted Region - Nusaf, A Mohamed; Kumaravel, R; Jayapragash, J (IAENG international journal of applied mathematics, 2024)
In India, there are myriad causes for air pollution, and celebrations of a festival like Bhogi also significantly pollute the air. This study aims to analyse the air quality in the regions of Chennai, India, during the Bhogi festival from 2019 to 2021, based on multiple air pollutants. The study introduces a hybrid approach, namely the Analytical Hierarchy Process - Entropy - Technique for Order Preference by Similarity to an Ideal Solution (AHP-Entropy-TOPSIS), to analyse and rank the areas based on the quality of air. A combined approach of AHP and Entropy is employed to determine the weights of multiple air pollutants. The TOPSIS approach ranks the city areas and identifies the area with the worst air quality during the festival. The proposed model is validated by performing the Spearman's rank correlation with three other existing Multi-Attribute Decision-Making (MADM) methods, namely Combinative Distance Based Assessment (CODAS), Weighted Aggregated Sum Product Assessment (WASPAS) and Multi-Objective Optimization on Basis of Ratio Analysis (MOORA). Sensitivity analysis is carried out to assess the effects of the priority weights and the dependency of the pollutants in ranking the regions. The highest air pollution level during the festival was seen in Ambattur (2019), Royapuram (2020), and Tondiarpet (2021) in their respective year. The results demonstrate the consistency and efficiency of the proposed approach.